Stress in Parents of Newborns in a Neonatal Intensive Care Unit - Kegler,Jaquiele Jaciara (2019)
Abstract Objective: To identify the level of stress and the most stressful situations for the parents of newborns hospitalized in a Neonatal Intensive Care Unit. Methods: A descriptive study, with a quantitative approach, performed with parents of newborns admitted to the Neonatal Intensive Care Unit. For the data collection, the Brazilian version of the Parental Stress Scale: Neonatal Intensive Care Unit (PSS: NICU) was used. The analysis was performed using descriptive statistics. Results: The change in the role of mother/father was the subscale in which the highest level of stress was obtained (mean=3.49) and the items considered more stressful in this subscale were "Separated from my baby" (mean=4.00) and "Feeling helpless and unable to protect my baby from pain and painful procedures" (mean=3.78). Conclusion: Hospitalization of a child in a neonatal unit is a stressful experience for parents and there are situations that trigger higher levels of stress.